SAFETY RULES IN THE PRODUCTION OF CAR MUFFLERS (Archive of Conferences, 2021)
Occupational safety in Uzbekistan is a social, economic, organizational, technical, sanitary-hygienic and medical prevention, which is based on the relevant laws and regulations, aimed at ensuring the safety, health and ability to work at work. Consists of a system of measures and means